Pengaruh kualitas siak terhadap kepuasan mahasiswa di stikes sukabumi menggunakan regresi linier - Muhammad Ramdani; Adhitia Erfina (Computer Science and Information Technology, 2023)
Introduction: Educational institutions in the era of rapid technological development must have an academic information system to support and support the process of teaching and learning activities, which must be measured through measuring the quality of academic information systems that can determine student satisfaction as users of academic information systems. Objective: This research was conducted to determine the effect of the quality of the academic information system on student satisfaction. Method: This type of research uses correlational research with a cross sectional approach. The population in this study were STIKES Sukabumi students with a sample of 298 using stratified random sampling techniques. The validity and reliability test in this study showed that all instrument items were valid with a strong enough to strong reliability. Univariate analysis uses frequency distribution with mean values, as well as bivariate analysis using multiple linear regression analysis. Results: This study shows that there is an influence on the quality of the academic information system on student satisfaction (p 0,000; b 0,957; R2 0,918, with equations Y=-6,320+0,957X+????). Conclusion: the quality of academic information systems can affect student satisfaction. Therefore, STIKES Sukabumi must always measure the quality of the academic information system in order to achieve student satisfaction as a user.